Rubber Price Effect on Exchange Rate: A Bayesian Mixture Model Approach - Phoong, Seuk Yen (Information Management and Business Review, 2013)
Mixture model is a probabilistic model that denotes the presence of subpopulations within an overall population meanwhile finite mixture model is a mixture model with finite-dimensional. In this paper, finite mixture model is applied and the application of Bayesian method to fit finite mixture model is popular and these application is adopt in the present study in order to explore the relationship between rubber price and exchange rate for Malaysia, Thailand, Philippines and Indonesia. Exchange rate plays leading role for a country because it represents the development for that country. The changes of exchange rate influence the flows of investment either the import or export prices for a nation’s. While another data set that adopt is rubber price. Rubber is an economic commodity that prospers in tropical climate. It is an important raw material because the latex that extracted is the primary source of natural rubber that enables to produce many useful products such as tires, surgical gloves, industrial hoses, rubber sheeting, industrial form parts and others household rubber products. Results found that rubber price effect on the change of exchange rate for Malaysia, Thailand, Philippines and Indonesia.